14
$\begingroup$

Evaluate: $$\lim_{n\to \infty }\sqrt[2]{2}\cdot \sqrt[4]{4}\cdot \sqrt[8]{8}\cdot \dots \cdot\sqrt[2^n]{2^n}$$

My attempt:First solve when $n$ is not infinity then put infinity in.

$$2^{\frac{1}{2}}\cdot 4^{\frac{1}{4}}\cdot \dots\cdot (2^n)^{\frac{1}{2^n}}$$

$$=2^{\frac{1}{2}}\cdot 2^{\frac{2}{4}}\cdot \dots\cdot 2^{\frac{n}{2^n}}$$

Now calculate the sum of the powers:

$$\frac{1}{2}+\frac{2}{4}+\frac{3}{8}+\dots+\frac{n}{2^n}$$

$$=\frac{2^{n-1}+2\cdot2^{n-2}+3\cdot2^{n-3}+\dots+n\cdot2^0}{2^n}$$

Now calculate the numerator:

$$2^0+2^1+2^2+\dots+2^{n-1}=2^n-1$$

$$+$$

$$2^0+2^1+\dots+2^{n-2}=2^{n-1}-1$$

$$+$$

$$2^0+2^1+\dots+2^{n-3}=2^{n-2}-1$$

$$+$$

$$\vdots$$

$$+$$

$$2^0=2^1-1$$

$$=2^1+2^2+2^3+\dots+2^n-n=2^{n+1}-n-1$$

Now put the numerator on the fraction:

$$\frac{2^{n+1}-n-1}{2^n}=2-\frac{n}{2^n}-\frac{1}{2^n}$$

Now we can easily find $\lim_{n \to \infty}\frac{1}{2^n}=0$

Then we just have to find $\lim_{n \to \infty }\frac{n}{2^n}$, that by graphing will easily give us the answer zero.

That gives the total answer is $4$.

But now they are two problems:

1.I cannot find $\lim_{n \to \infty }\frac{n}{2^n}$ without graghing.

2.My answer is too long.

Now I want you to help me with these problems.Thanks.

$\endgroup$
  • 1
    $\begingroup$ Hint: use that $\log(ab)=\log(a)+\log(b)$ and convert it into a summation (series) problem. $\endgroup$ – Fimpellizieri Aug 5 '16 at 20:10
  • $\begingroup$ @Fimpellizieri We didn't learn logarithem yet. $\endgroup$ – Taha Akbari Aug 5 '16 at 20:11
  • 1
    $\begingroup$ Idk why no one has mentioned this yet, but $\sum \frac{n}{2^n}$ looks an awful lot the series expansion of $\left(\frac{1}{1-x}\right)^2$, it's just missing a factor of $x$, that is $x\left(\frac{1}{1-x}\right)^2$. So $\sum \frac{n}{2^n}=\frac{1}{2}\frac{1}{1/4}=2$, since $|1/2|<1$. $\endgroup$ – Nobody Aug 5 '16 at 20:52
  • $\begingroup$ thanks for showing your work, +1 $\endgroup$ – Arjang Aug 6 '16 at 1:43
  • $\begingroup$ It seems weird to have limits introduced but not logarithms. $\endgroup$ – Batman Aug 6 '16 at 1:52
28
$\begingroup$

$$I=\frac{1}{2}+\frac{2}{4}+\frac{3}{8}+\frac{4}{16}+\frac{5}{32}+\frac{6}{64}+\cdots$$ $$2I=1+1+\frac{3}{4}+\frac{4}{8}+\frac{5}{16}+\frac{6}{32}+\cdots$$ $$2I-I=1+\left(1-\frac 12 \right)+\left(\frac 34 -\frac 24 \right)+\left(\frac 48 -\frac 38 \right)+\left(\frac {5}{16} -\frac {4}{16} \right)+\cdots$$ $$I=1+\frac 12+\frac 14+\frac 18+\cdots=2$$ therefore $$\lim_{n\to \infty }\sqrt[2]{2}\times\sqrt[4]{4}\times\sqrt[8]{8}\times\dots\times\sqrt[2^n]{2^n}=2^2=4$$

$\endgroup$
  • 3
    $\begingroup$ Nice answer it is too much short and easy to under stand +1. $\endgroup$ – Taha Akbari Aug 5 '16 at 20:13
  • $\begingroup$ Would you be so kind as to explain the "therefore"? I'm having trouble seeing the jump which apparently is obvious. O_o $\endgroup$ – John Aug 5 '16 at 21:28
  • 6
    $\begingroup$ @John $\sqrt[2]{2}\times\sqrt[4]{4}\times\sqrt[8]{8}\times\dots=2^{\frac 12+\frac 24+\frac 38+\cdots}=2^2=4$ $\endgroup$ – Behrouz Maleki Aug 5 '16 at 21:30
  • 4
    $\begingroup$ Incredibly clever! $\endgroup$ – John Aug 5 '16 at 21:32
  • $\begingroup$ @John Please. So thanks. $\endgroup$ – Behrouz Maleki Aug 5 '16 at 21:33
11
$\begingroup$

I believe this is a "known" representation of the key summation:

enter image description here

$$\sum_{n=1}^{\infty} \frac{n}{2^n} \;=\; \frac{1}{2} + \left( \frac{1}{4} + \frac{1}{4} \right) + \left( \frac{1}{8} + \frac{1}{8} + \frac{1}{8} \right) + \cdots \;=\; 2 $$

$\endgroup$
4
$\begingroup$

I hope this would be useful for you.

So your trying to evaluate $\displaystyle\prod_{n=1}^{\infty}\sqrt[2^{n}]{2^{n}}$. Consider first $\displaystyle\prod_{n=1}^{k}\sqrt[2^{n}]{2^{n}}=2^{\sum_{n=1}^{k}\frac{n}{2^{n}}}$, after developing the product properly. Now you have to make sense of $$\lim_{k\to\infty}\sum_{n=1}^{k}\frac{n}{2^{n}}$$ , so to reach a specific value, note that $\sum_{n=1}^{k}\frac{n}{2^{n}}=\sum_{n=1}^{k}\frac{n-1}{2^{n-1}}-\frac{n}{2^{n}}+\sum_{n=1}^{k}\frac{1}{2^{n-1}}$, therefore

\begin{eqnarray*} \lim_{k\to\infty}\sum_{n=1}^{k}\frac{n}{2^{n}}&=&\lim_{k\to\infty}\sum_{n=1}^{k}\frac{n-1}{2^{n-1}}-\frac{n} {2^{n}}+\sum_{n=1}^{k}\frac{1}{2^{n-1}}\\ &=&\lim_{k\to\infty}-\frac{k}{2^{k}}+\frac{1-\frac{1}{2^{k+1}}}{1-\frac{1}{2}}\\ &=&2 \end{eqnarray*} Finally $$\prod_{n=1}^{\infty}\sqrt[2^{n}]{2^{n}}=\lim_{k\to\infty}\prod_{n=1}^{k}\sqrt[2^{n}]{2^{n}}=\lim_{k\to\infty}2^{\sum_{n=1}^{k}\frac{n}{2^{n}}}=2^{\lim_{k\to\infty}\sum_{n=1}^{k}\frac{n}{2^{n}}}=2^{2}=4$$

$\endgroup$
  • $\begingroup$ Even though, it solves the problem, it doesn't answer your question, sorry for that. $\endgroup$ – Cristian Baeza Aug 5 '16 at 20:48
  • $\begingroup$ I don't really want the answer of question I wanted a shorter answer.+1 $\endgroup$ – Taha Akbari Aug 6 '16 at 5:07
2
$\begingroup$

$$\text{P}=\prod_{n=1}^{\infty}\sqrt[2^n]{2^n}=\sqrt[2]{2}\times\sqrt[4]{4}\times\sqrt[8]{8}\times\dots=2^{\frac{1}{2}}\times4^{\frac{1}{4}}\times8^{\frac{1}{8}}\times\dots$$

When we use the LOG function get (when $n$ is positive):

$$\ln\left(\left(2^n\right)^{\frac{1}{2^n}}\right)=\frac{n\ln(2)}{2^n}$$

And using, when $a$ and $b$ are positive:

$$\ln(ab)=\ln(a)+\ln(b)$$

So, we get that:

$$\ln(\text{P})=\frac{1\ln(2)}{2^1}+\frac{2\ln(2)}{2^2}+\frac{3\ln(2)}{2^3}+\dots=\ln(2)\left[\frac{1}{2^1}+\frac{2}{2^2}+\frac{3}{2^3}+\dots\right]$$

And, now we know that:

$$\sum_{n=1}^{\infty}\frac{n}{2^n}=\frac{1}{2^1}+\frac{2}{2^2}+\frac{3}{2^3}+\dots=\frac{2}{(2-1)^2}=2$$

Using, when $|x|>1$:

$$\sum_{n=1}^{\infty}\frac{n}{x^n}=\frac{x}{(x-1)^2}$$

So:

$$\ln(\text{P})=\ln(2)\left[2\right]=2\ln(2)\Longleftrightarrow\text{P}=4$$

We, find the answer:

$$\color{red}{\text{P}=\prod_{n=1}^{\infty}\sqrt[2^n]{2^n}=\sqrt[2]{2}\times\sqrt[4]{4}\times\sqrt[8]{8}\times\dots=2^{\frac{1}{2}}\times4^{\frac{1}{4}}\times8^{\frac{1}{8}}\times\dots=4}$$

$\endgroup$
  • $\begingroup$ OP says they did not learn logarithms yet and anyway logarithms are not useful to solve these, only the rule $a^xa^y=a^{x+y}$ is. Are these the reasons why you focus on logarithms? $\endgroup$ – Did Aug 10 '16 at 9:50
  • $\begingroup$ Not usefull do not mean, wrong! And there was an answer that have a more easy way, what I did is just another way! $\endgroup$ – Jan Aug 10 '16 at 9:54
  • $\begingroup$ Right, "not useful" means "not useful". By the way, do you seriously think that drawing the identity $\sum\limits_{n=1}^{\infty}\frac{n}{x^n}=\frac{x}{(x-1)^2}$ out of the hat makes for a good post (i) for the OP, (ii) for other users? The intersection of the populations of users who need an answer and who understand this step might be empty... $\endgroup$ – Did Aug 10 '16 at 9:57
1
$\begingroup$

$I=1+\frac 12+\frac 14+\frac 18+\frac 1{16}+\cdots=2$

$I^2 =1+\frac{2}{2}+\frac{3}{4}+\frac{4}{8}+\frac{5}{16}+\cdots$

$I^2 -I=\frac{1}{2}+\frac{2}{4}+\frac{3}{8}+\frac{4}{16}+\cdots=2^2-2=2$

Then

$\lim_{n\to \infty }\sqrt[2]{2}\cdot \sqrt[4]{4}\cdot \sqrt[8]{8}\cdot \dots\cdot \sqrt[2^n]{2^n}=2^{I^2-I}=2^2=4$

$\endgroup$
  • 2
    $\begingroup$ The second line might require some explanation but I got it +1 ;) $\endgroup$ – Peter Franek Aug 6 '16 at 9:07
1
$\begingroup$

A standard thing to do to, is too use the commonly known geometric series formula, and set:

$$f(x)=\sum_{n=0}^{\infty} x^n=\frac{1}{1-x}$$

The formula is not hard to prove, and it holds for $|x|<1$ (which can be seen by the ratio test for convergence) we take $x \in (-1,1)$.

Then by term by term differentiation we get:

$$f'(x)=\sum_{n=1}^{\infty} nx^{n-1}=\frac{1}{x}\sum_{n=1}^{\infty} nx^n=\frac{1}{(1-x)^2}$$

Hence we have:

$$\sum_{n=1}^{\infty} nx^n=\frac{x}{(1-x)^2}$$

And the case your interested about is $x=\frac{1}{2}$

$\endgroup$
0
$\begingroup$

I would like to generalize Behrouz' rather nifty answer:

$$I=\sum_{n=1}^{\infty} \frac{n}{r^n}=\frac{1}{r}+\frac{2}{r^2}+\frac{3}{r^3}+\frac{4}{r^4}$$ The key is now to multiply everything by $r$:

$$rI=1+\frac{2}{r}+\frac{3}{r^2}+\frac{4}{r^3}$$ Now we calculate $rI-I$ $$rI-I=1+(\frac{2}{r}-\frac{1}{r})+(\frac{3}{r^2}-\frac{2}{r^2})+(\frac{4}{r^3}-\frac{3}{r^3})+...$$ simplifies to

$$1+\frac{1}{r}+\frac{1}{r^2}+\frac{1}{r^3}+\frac{1}{r^4}...$$ And that is our good old geometric sum

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.